Corneal morphology and visual outcomes in LASIK patients after orthokeratology: a pilot study - Queirós, A. (2018)
A STATEMENT OF SIGNIFICANCE: For the first time, this study shows that corneas that previous undergone orthokeratology treatment do not respond differently to LASIK compared with previous soft contact lens wear experience. PURPOSE: To evaluate and compare the corneal morphology and visual outcomes of long-term soft and orthokeratology (OK) contact lens fitting in wearers undergoing corneal refractive surgery (LASIK) for myopia correction. METHODS: Sixteen (16) myopic patients wearing hydrophilic soft contact lens (SCL, n = 8 subjects, control group) and OK (n = 8 subjects, OK group) lenses who undergone LASIK were retrospectively evaluated. Preoperative fitting of contact lenses and one year postoperative were studied using Pentacam (Oculus, Inc. GmbH, Wetzlar, Germany). Corneal pachymetry and volume, corneal topography, anterior and posterior surface elevation data and the anterior surface aberrometry of the cornea were recorded and used for fitting. RESULTS: Age, refractive error and topographic parameters before LASIK did not showed statistically significant differences between the two study groups. LASIK post-treatment results showed identical changes in both control and OK groups and did not show significant differences in all the parameters evaluated. The changes on corneal parameters and HOA due to refractive surgery intervention were not different between Control and OK group (p > 0.050). CONCLUSIONS: Corneal changes due to OK treatment are reversible after its discontinuation. The present study gives an overview of how OK does not impair future LASIK surgery for the correction of myopia and does not influence the success/results of such intervention. These findings suggest that OK CL wear does not change corneal biomechanics and does not compromise a possible LASIK refractive surgery. Although this is a pilot study and there is a need of evaluate this results/changes in future studies.